Sorting, status, and shadow education: How track placement shapes parental investment - Thilo Klein; Sarah McNamara (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Educational tracking-separating students into tracks or schools by ability-is commonplace, but access and preferences for top programs often depend on socioeconomic status (SES), reinforcing inequality. We study shadow education in the context of an early-tracking system, exploiting score cut-offs using a pseudo-regression discontinuity design to isolate the causal effect on parental investments. We find that assignment to the highest track disproportionately increases private tutoring among families in the lowest tercile of SES. This suggests tracking activates a behavioral response among disadvantaged households, which may amplify between-track achievement gaps.
Keywords: I21; I24; I28; E47; C26; 330; education; school choice; tracking; shadow education; private tutoring; student achievement; inequality of opportunity